Wearables in epilepsy and Parkinson's disease—A focus group study. (16th July 2017) - Ozanne, A.; Johansson, D.; Hällgren Graneheim, U.; Malmgren, K.; Bergquist, F.; Alt Murphy, M.
Abstract : Objectives: Wearable sensors that measure movement and physiological variables are attractive for clinical evaluation of neurological diseases such as epilepsy and Parkinson's disease (PD). The aim of this study was to explore perceptions regarding the use of wearable technology in disease monitoring and management as reported by individuals with epilepsy and Parkinson's disease as well as health professionals working with these patient groups. Materials and Methods: Six patient groups (n=25) and two groups with health professionals (n=15) participated in this qualitative, descriptive study with focus group interviews. A manifest qualitative content analysis was used. Results: Four categories and nine subcategories emerged from the analysis. Participants saw possible benefits for improved treatment effect and valued this benefit more than possible inconvenience of wearing the sensors. Discrete design and simplicity were considered as facilitators for improved usability. They emphasized the importance of interactive information between patients and health professionals. However, they were concerned about unclear information and inconclusive recordings and some fears about personal integrity were at odds with the expectations on interactivity. Conclusions: Patients need to feel well informed and find an added value in using wearables. Wearables need to be user‐friendly, have an attractive design, and show clinical efficacy in improving disease management. Variations in perceptions regarding integrity, benefits, and effectiveness of monitoring indicate possible conflicts of expectations among participants. The engagement of end users, patients, and health professionals, in the design and implementation process, is crucial for the development of wearable devices that enhance and facilitate neurological rehabilitation practice.